(untitled) (Південний архів (історичні науки), 2023)
Purpose. The work aims to analyze the activities of leading educators of the Ukrainian Institute of Social Studies. The article focuses on the institution’s activities, as it played an important role in educational services to Ukrainian emigrants from 1926 to 1928. Methods. While studying this issue, the historical process was applied as a main one, as well as analytical and descriptive. To understand the effective activity of the teaching staff at an educational institution, it is necessary to single out certain personalities and use their example to demonstrate the core of science and describe educational activities. Results: Distinguished researchers, with the help of a systematic analysis and historical method, noted their academic achievements and influence on the development of Ukrainian science abroad during emigration. Conclusions: Effective self-realization of teachers in emigration primarily depends on creative potential, self-control, professional competencies, and educational strategies. The source base for the study of the brightest and most productive personalities of the Ukrainian Institute of Social Studies is a diverse structure of documents, among them we highlight the report on the activities of the academic institution, articles, and archival documents that note the educational activities of teachers. The characteristics of this institution’s main teachers are M. Shapoval, N. Grigoriyev, S. Rusova, L. Bilecki, S. Goldelman, O. Eichelman, S. Sheluhin, M. Mandryk, T. Hryb, who accumulated academically and scientific process in the institution. Scientific offices of professors from various disciplines: economics, sociology, law and ethnology are outlined. It has been established that knowledge is the most valuable treasure in society, and with the help there is an exchange of information between the old and new generations. It is necessary to consider the Ukrainian Institute of Public Studies as an educational institution that formed the scientific potential of Ukraine outside the country because, in the future, the specialists who received the education will try to return to the territory of Ukraine and implement educational reforms. So, social transformations lead to radical changes in the higher education system.